Aplikasi Metode Thomas untuk Mengefisiensikan Penyelesaian Sistem Persamaan Linier pada Persoalan Perambatan Panas dengan Skema Implisit - Supriyono Supriyono; Eka Haraiba (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2004)
Equation spread thermal was an issued which on the equation of differentially partialparabolic. For finished that equation, one method used for were different method to whichimplicit scheme. Degradation of implicit scheme in equation spread thermal produced linierequation system form with matrix was tridiagonal matrix. Linier equation system numericallyprocessed was Gauss-Jordan method. If Step Measurement ( t and x ) on equation spreadthermal was very small, whereas observing interval and time was bigger. It will made bigmeasure of linier equation system. Finally, completion execution time with Gauss-Jordanmethod was longer. To reduce completion execution time linier equation system with thoseGauss-Jordan methods, it necessary to putted another method, which is Thomas method. Theefficient step was to decrease linier equation system measure with Thomas method and a newlinier equation system finished with Gauss-Jordan method. Results of the research showedthat execution time between combined method of Thomas method and Gauss-Jordan methodin accordance Gauss-Jordan had significantly different. The bigger different linier equationsystem the bigger time they operated. For example, to system matrix 2525 x 2525 the different03: 05: 760 compared to 33: 55: 490. In this research we also discussed algorithm complexityand study results showed that 2525 x 2525 mix of Thomas method and Gauss-Jordan methodis 2.031.105.803 loop and with Gauss-Jordan loop 16.164.813.274.Kata kunci: persamaan, perambatan, panas, implisit, matriks, tridiagonal, metode Thomas,efisien.